Acupuncture therapy for radiotherapy-induced adverse effect: A systematic review and network meta-analysis - Wu, Tong; Fu, Chengwei; Deng, Yiran; Huang, Wanping; Wang, Jieyu; Jiao, Yang (Frontiers in Public Health, 2022)
Objective To evaluate the efficacy of different acupuncture therapies for radiotherapy-induced adverse effect (RIAE) and find out the optimal scheme. Methods Eligible randomized controlled trials (RCTs) were collected from inception to June 2020, from 9 bibliographic databases. Risk of bias evaluation of analyzed literature was carried out by Cochrane risk-of-bias tool. Network meta-analysis was mainly performed by STATA 14.2 and OpenBUGS 3.2.3 through figuring out the network diagrams, league figures, and SUCRA values. Results Forty-one studies with 3011 participants reported data suitable for network meta-analysis. Twenty articles of them had a low to moderate risk of bias. ST36 was the most widely used in acupoint prescription. Four outcome indicators were described based on network meta-analysis: acupuncture+medication ranked first in treating radiation enteritis, moxibustion+medication ranked first in preventing radiotherapy-induced leukopenia, acupuncture+medication ranked first in preventing radioactive oral mucositis, acupuncture ranked first in improving stimulated salivary flow rate of radioactive xerostomia. Conclusion The findings of network meta-analysis manifested that acupuncture therapy combined with medication has superiority in most RIAEs, both reducing incidence and relieving symptoms. However, high-quality studies are still needed to provide conclusive evidence.